2010
DOI: 10.1590/s1519-566x2010000500020
|View full text |Cite
|
Sign up to set email alerts
|

Vectorial capacity of Triatoma guasayana (Wygodzinsky & Abalos) (Hemiptera: Reduviidae) compared with two other species of epidemic importance

Abstract: -Triatoma guasayana (Wygodzinsky & Abalos) is a peridomestic triatomine with epidemiological importance in Bolivia, that may play an important role in the transmission of Trypanosoma cruzi (Chagas). In this study, two parameters of vectorial capacity were evaluated: the interval of feeding-defecation time and metacyclogenesis, in adult males and females and nymphal instars II to V of T. guasayana with comparisons with Triatoma infestans (Klug) and T. sordida (Stal). The results showed a close relationship betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
4
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 36 publications
0
17
4
2
Order By: Relevance
“…For instance, fifth-instar T. sordida and T. guasayana need to eat an average minimum of 60-100 and 115 mg of blood, respectively, for defecation to occur during feeding or soon thereafter. 23,33 In our experiments, although 52% of fifth-instar T. rubida ingested more than 100 mg of blood, we found that only 18% of those insects defecated while feeding. We also found that most female T. rubida ate 114 ± 9 mg (mean ± SE; median = 117 mg) of blood, which is more than the amount reportedly required for defecation to occur during feeding in female T. sordida and T. guasayana .…”
Section: Discussioncontrasting
confidence: 50%
See 3 more Smart Citations
“…For instance, fifth-instar T. sordida and T. guasayana need to eat an average minimum of 60-100 and 115 mg of blood, respectively, for defecation to occur during feeding or soon thereafter. 23,33 In our experiments, although 52% of fifth-instar T. rubida ingested more than 100 mg of blood, we found that only 18% of those insects defecated while feeding. We also found that most female T. rubida ate 114 ± 9 mg (mean ± SE; median = 117 mg) of blood, which is more than the amount reportedly required for defecation to occur during feeding in female T. sordida and T. guasayana .…”
Section: Discussioncontrasting
confidence: 50%
“…Similarly, it was also reported that adult males of Panstrongylus megistus and Triatoma barberi , and nymphs of Triatoma guasayana and Triatoma vitticeps , do not defecate while feeding. 17,23,32 Although we found that most juvenile insects and none of the adult males defecated while feeding, transmission of the parasite to humans can occur if the engorged insects remain in close contact with the host after feeding, possibly defecating and urinating to eliminate the extra weight gained during a blood meal. 18 Indeed, it has been proposed that triatomines that defecate within 10 minutes after the end of feeding are potentially effective vectors of T. cruzi .…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Sin embargo, debido a que algunos triatominos silvestres pueden llegar al peridomicilio o hacer intrusiones dentro del domicilio, es necesario tener en cuenta las características de su biología que favorezcan su competencia vectorial. Esta última se entiende como la habilidad de un vector (artrópodo o molusco) para transmitir un agente patógeno mediante diversos factores determinantes biológicos, como: supervivencia; características anatómicas, especialmente del aparato bucal y sistema digestivo; características fisiológicas, como la cantidad de sangre ingerida y el tiempo de emisión de la primera deyección en el caso de insectos que ya se encuentran infectados; además de características genéticas de los vectores, como la propensión a la infección por las distintas unidades discretas de tipificación (Discrete Unit of Typification, DTU) de T. cruzi (2,3) Los vectores de T. cruzi pueden dividirse en vectores primarios, o principales, y secundarios. Las especies consideradas vectores primarios son aquellas que pueden colonizar las viviendas en altas densidades, tienen acentuada antropofilia y altas tasas de infección con T. cruzi.…”
unclassified